Efektivitas Pelaksanaan Program Pendaftaran Tanah Sistematis Lengkap (PTSL) Dalam Penerbitan Sertifikat Tanah Di Kantor Pertanahan Kabupaten Deli Serdang - Alfisa Rizky Zatira; Muhammad Husni Thamrin (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
Land has an important meaning in human life, this is because almost all aspects of human life cannot be separated from the existence of land. Every year population growth increases, resulting in an increase in the need for land and results in an increase in problems related to the land sector. Problems that often occur make the government issue a policy to make it easier for the community to process land certificates, namely the Complete Systematic Land Registration (PTSL) program in Article 3 paragraph (4) of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 6 of 2018 concerning Acceleration of the implementation of Complete Systematic Land Registration (PTSL). The method used in this study is descriptive qualitative with data collection techniques in the form of interviews, observation and documentation. The results of the research conclude that the effectiveness of the implementation of the Complete Systematic Land Registration program in Issuing Land Certificates at the Land Office of Deli Serdang Regency has been carried out. Judging from the achievement of the goals within the period of time that was carried out in a year and there are still several certificates that have not been issued. Process integration in its implementation has also been carried out and the socialization that has been carried out has not been said to be successful because the socialization is carried out only in villages that are selected to be carried out annually, so not many people know about the complete systematic land upgrading program. In adaptation to increasing the capacity of land office employees, capacity building is not carried out because the process of implementing the complete systematic land registration program is the same as usual activities and the infrastructure used by employees to get off the ground has already been provided by the land office.